LANGUAGE LEARNING STRATEGIES AND ACADEMIC ACHIEVEMENT OF ENGLISH DEPARTMENT STUDENTS - Wulan Agustin; Achmad Yudi Wahyudin; Shaleha Isnaini (Faculty of Arts and Education, 2021)
In mastering English, students of English Department need to use language learning strategies while they also should pay attention to their academic achievement. As language learning strategies are relevant to the students’ effort to achieve the high-grade academic achievement, this study aims to determine the relationship between language learning strategies use and the students’ academic achievement indicated by grade point average (GPA). The method used in this research is quantitative research, employing documentation and questionnaires. The sample in this study were 38 students of English Department at one of private universities in Indonesia. From the result of this study, it can be concluded that there is a positive relationship between the language learning strategies use and students’ academic achievement. The pedagogical implications are related to the suggestion for English teachers to introduce and train the English Department students to use language learning strategies to improve their academic achievement.